Species roles in plant–pollinator communities are conserved across native and alien ranges. Issue 8 (23rd June 2016) - Emer, Carine; Memmott, Jane; Vaughan, Ian P.; Montoya, Daniel; Tylianakis, Jason M.
Abstract: Aim: Alien species alter interaction networks by disrupting existing interactions, for example between plants and pollinators, and by engaging in new interactions. Predicting the effects of an incoming invader can be difficult, although recent work suggests species roles in interaction networks may be conserved across locations. We test whether species roles in plant–pollinator networks differ between their native and alien ranges and whether the former can be used to predict the latter. Location: World‐wide. Methods: We used 64 plant–pollinator networks to search for species occurring in at least one network in its native range and one network in its alien range. We found 17 species meeting these criteria, distributed in 48 plant–pollinator networks. We characterized each species' role by estimating species‐level network indices: normalized degree, closeness centrality, betweenness centrality and two measures of contribution to modularity ( c‐ and z‐ scores). Linear mixed models and linear regression models were used to test for differences in species role between native and alien ranges and to predict those roles from the native to the alien range, respectively. Results: Species roles varied considerably across species. Nevertheless, although species lost their native mutualists and gained novel interactions in the alien community, their role did not differ significantly between ranges. Consequently, closeness centrality and normalized degree in the alien range were highly predictable from the native range networks. Main conclusions: Species with high degree and centrality define the core of nested networks. Our results suggest that core species are likely to establish interactions and be core species in the alien range, whilst species with few interactions in their native range will behave similarly in their alien range. Our results provide new insights into species role conservatism and could help ecologists to predict alien species impact at the community level.